Dyspareunia and childbirth: a prospective cohort study. (21st January 2015) - McDonald, EA; Gartland, D; Small, R; Brown, SJ
Abstract : Objective: To investigate the relationship between mode of delivery, perineal trauma and dyspareunia. Design: Prospective cohort study. Setting: Six maternity hospitals in Melbourne, Australia. Sample: A total of 1507 nulliparous women recruited in the first and second trimesters of pregnancy. Method: Data from baseline and postnatal questionnaires (3, 6, 12 and 18 months) were analysed using univariable and multivariable logistic regression. Main outcome measure: Study‐designed self‐report measure of dyspareunia at 18 months postpartum. Results: In all, 1244/1507 (83%) women completed the baseline and all four postpartum questionnaires; 1211/1237 (98%) had resumed vaginal intercourse by 18 months postpartum, with 289/1211 (24%) women reporting dyspareunia. Compared with women who had a spontaneous vaginal delivery with an intact perineum or unsutured tear, women who had an emergency caesarean section (adjusted odds ratio [aOR] 2.41, 95% confidence interval [95% CI] 1.4–4.0; P = 0.001), vacuum extraction (aOR 2.28, 95% CI 1.3–4.1; P = 0.005) or elective caesarean section (aOR 1.71, 95% CI 0.9–3.2; P = 0.087) had increased odds of reporting dyspareunia at 18 months postpartum, adjusting for maternal age and other potential confounders. Conclusions: Obstetric intervention is associated with persisting dyspareunia. Greater recognition and increased understanding of the roles of mode of delivery and perineal trauma in contributing to postpartum maternal morbidities, and ways to prevent postpartum dyspareunia where possible, are warranted.